2019
DOI: 10.1007/s10295-019-02236-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the ZRT, IRT-like protein (ZIP) family genes reveal their involvement in growth and kojic acid production in Aspergillus oryzae

Abstract: The ZRT, IRT-like protein (ZIP) family exists in many species and plays an important role in many biological processes, but little is known about ZIP genes in Aspergillus oryzae. Here, 10 ZIP genes in A. oryzae were identified and these were classified into four groups based on phylogenetic analysis. The structures of these AoZip genes were determined, which indicated a great divergence of AoZip members from different groups. Synteny analysis revealed that AoZip7, AoZip8, and AoZip10 are conserved among Asperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…A possible explanation for this is whether overexpression AoNramp1 or knockout of AoNramp1 both disrupt metal ion homeostasis and A. oryzae is sensitive to the variety of metal ions. In line, overexpression and disruption of Nramp gene bring about changes in metal ion concentration of cells and metal ions have a great influence on the growth of A. oryzae (Fejes et al 2020;Zhang et al 2019;Ishimaru et al 2012;Mori et al 2018;Cohen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible explanation for this is whether overexpression AoNramp1 or knockout of AoNramp1 both disrupt metal ion homeostasis and A. oryzae is sensitive to the variety of metal ions. In line, overexpression and disruption of Nramp gene bring about changes in metal ion concentration of cells and metal ions have a great influence on the growth of A. oryzae (Fejes et al 2020;Zhang et al 2019;Ishimaru et al 2012;Mori et al 2018;Cohen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the inducer of AoNramp1 promoter is Zn 2+ or Mn 2+ . Our previous study has revealed that a certain metal concentration of Zn 2+ or Mn 2+ doesn't repress the growth of A. oryzae (Zhang et al 2019), which makes AoNramp1 promoter more advantageous than the copper-inducible promoter. However, it still needs to determine suitable inducers (Zn or Mn) and the optimal metal concentration for practical use, and further study is required to investigate the functional characterization of AoNramp1 promoter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some (mutations Bscl2, Agpat2) there is a reduction in marrow fat via MRS ( 22 24 ); while in others (mutations CAV1, LMNA) a preservation of BMAT is noted ( 25 , 26 ). Mouse models like A-ZIP fat-less ( 27 ), Cav1 (-/-) ( 28 ), transgenics applying diphtheria toxin to ablate adipocytes ( 29 ) or PPARγ (+/-) ( 30 ), reveal increased bone quantity or osteosclerosis. The precise effect of CGL generally, and specifically that of Bscl2/SEIPIN deficiency on bone, remains essentially unknown.…”
Section: Introductionmentioning
confidence: 99%